An intelligent aid for the visually handicapped - Toh, Jia Min (Nanyang Technological University, 2023)
The aim of the project is to develop an indoor navigational assistance technological aid for the blind or visually handicapped which is to be relatively inexpensive for both the blind and the businesses that equipped their buildings. For example, some malls, even though have building maps, are usually stationary displays that are useful only when one can locate and read the display. It is already challenging for a sighted person. The task of finding a way in such a building for an unassisted person with visual impairment is almost impossible without human assistance. This project requires a survey of the existing aids and the requirements of users, and also to carry out the design and construction of something that is useful for the above mentioned purpose. This project contemplates a student identifying a need, preparing a performance specifications and undertaking the design and implementation of the project. Students with strong interest and background in electronics and hardware are encouraged.